2017
DOI: 10.1039/c7ra00833c
|View full text |Cite|
|
Sign up to set email alerts
|

Growth behavior of water dispersed MgAl layered double hydroxide nanosheets

Abstract: A diagram divided into three regions was made to determine the state of LDH nanosheets in aqueous phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…We speculate that this is the dominant mechanism in concentrated, rapidly mixed conditions and may be a significant crystallization pathway during aging. This confirms the previous studies that have suggested an OA mechanism 24 , 29 in addition to Ostwald ripening, a slow dissolution, and recrystallization process 22 , 50 .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…We speculate that this is the dominant mechanism in concentrated, rapidly mixed conditions and may be a significant crystallization pathway during aging. This confirms the previous studies that have suggested an OA mechanism 24 , 29 in addition to Ostwald ripening, a slow dissolution, and recrystallization process 22 , 50 .…”
Section: Resultssupporting
confidence: 92%
“…The correlation between aspect ratio and height indicates that the particles assemble in an ordered manner, which directly verifies previous studies that have suggested that LDH particles may preferentially orient epitaxially, edge-to-edge 45 and face-to-face 24 . More interestingly, the non-monotonic dependence of aspect ratio and shear suggests that shear not only influences the kinetics of OA but also has competing effects that enhance or decrease particle anisotropy.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…10,11 The reversible electrostatic adsorption /desorption on the electrode surface is used to store the charge. 12 By arrangement of the opposite sign charge an electric double layer is formed in the vicinity of the electrode/electrolyte interface, a so-called "electric double layer capacitor".…”
mentioning
confidence: 99%
“…The Mg 2 Al-LDH platelets grow both in diameter and in thickness while dispersed in water, which is a result of particle agglomeration and Ostwald ripening. 28,29 The PVA polymer chains may act as particle growth inhibitors attaching to the surface of an LDH platelet. Thus, in a mixed Mg 2 Al-LDH NS/PVA dispersion, the aspect ratio of the Mg 2 Al-LDH NS is stable.…”
Section: Materials Horizons Communicationmentioning
confidence: 99%